PERLINDUNGANHAK CIPTA TERHADAP PENGGANDAANPERMAINAN VIDEO - Wibowo, Ahmad Fajri (Jurnal Hukum & Pembangunan, 2021)
2020AbstractCopyright protection is one of the systemsfor providing legal protection in creative industry. One of the creative industry that need copyright protection is video game industry. Developmentofvideo games in indonesia is very fast, therefore legal protection is needed to maintain the development of video game industry. Basically video game is an object of creation in indonesian copyright law number 28 year 2014 concerning copyright. In the development of the video game industry, there are problems that occur such as many copying of video game illegally. Thus, copyright protection have a significant role in protecting the video game industry.